2015
DOI: 10.1063/1.4916760
|View full text |Cite
|
Sign up to set email alerts
|

Stress and structural damage sensing piezospectroscopic coatings validated with digital image correlation

Abstract: The piezospectroscopic effect, relating a material’s stress state and spectral signature, has recently demonstrated tailorable sensitivity when the photo-luminescent alpha alumina is distributed in nanoparticulate form within a matrix. Here, the stress-sensing behavior of an alumina-epoxy nanoparticle coating, applied to a composite substrate in an open hole tension configuration, is validated with the biaxial strain field concurrently determined through digital image correlation. The coating achieved early de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…An open-hole tension (OHT) carbon fiber reinforced polymer (CFRP) substrate with a PS coating consisting of 20 vol% of α-alumina nanoparticles in epoxy matrix was manufactured and tested. The coating detected internal ply damage at 76 % failure load, which was well before it surfaced at 92 % failure load as measured by digital image correlation (DIC) [9].…”
Section: Stress and Damage On The Surface And Subsurfacementioning
confidence: 69%
See 1 more Smart Citation
“…An open-hole tension (OHT) carbon fiber reinforced polymer (CFRP) substrate with a PS coating consisting of 20 vol% of α-alumina nanoparticles in epoxy matrix was manufactured and tested. The coating detected internal ply damage at 76 % failure load, which was well before it surfaced at 92 % failure load as measured by digital image correlation (DIC) [9].…”
Section: Stress and Damage On The Surface And Subsurfacementioning
confidence: 69%
“…However, it was reported that 38 vol% of α-alumina is the maximum limit to be added to a polymer matrix to improve its mechanical properties [8]. Freihofer et al [9] demonstrated the capability of PS coatings in monitoring stress on a composite laminate substrate when it is subjected to load and detecting damage before failure occurs. An open-hole tension (OHT) carbon fiber reinforced polymer (CFRP) substrate with a PS coating consisting of 20 vol% of α-alumina nanoparticles in epoxy matrix was manufactured and tested.…”
Section: Stress and Damage On The Surface And Subsurfacementioning
confidence: 99%
“…Spatial measurements of substrate strain and PS shift were obtained simultaneously for the first time in an novel experiment [23]. The PS relationships originate from the distortion of the Ligand field around the Cr 3 þ substitutional impurity within the Al 2 O 3 lattice.…”
Section: Multiscale Mechanics To Model the Ps Responsementioning
confidence: 99%
“…The applications of piezospectroscopy have recently been expanded by the fabrication of alumina-epoxy nanocomposites with tailorable mechanical and PS properties [20]. This produced a material which can be applied as a compliant coating to structures for stress sensing [21][22][23]. In the process of holistically understanding the multi-scale mechanics of these new materials, the solution of an effective elastic modulus of the nanocomposite with the experimental PS response was discovered [24].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a carbon fiber composite modified with additional nanoparticles is commonly referred to as a hybrid carbon fiber reinforced polymer (HCFRP). Whether in high performing composites or other applications, particle dispersion is important for many properties, including strength, modulus, and fracture toughness [12][13][14][15][16][17][18][19][20][21]. While there are a few methods to improve dispersion, such as the use of ultrasonic waves [22], achieving good dispersion of nanoparticles is known to be very difficult, with challenges such as agglomerations and sedimentation often encountered at high particle loadings [20].…”
Section: Introductionmentioning
confidence: 99%